2011
DOI: 10.1007/s10661-011-2181-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating vertebrate, benthic macroinvertebrate, and diatom taxa richness in raftable Pacific Northwest rivers for bioassessment purposes

Abstract: The number of sites sampled must be considered when determining the effort necessary for adequately assessing taxa richness in an ecosystem for bioassessment purposes; however, there have been few studies concerning the number of sites necessary for bioassessment of large rivers. We evaluated the effect of sample size (i.e., number of sites) necessary to collect vertebrate (fish and aquatic amphibians), macroinvertebrate, and diatom taxa from seven large rivers in Oregon and Washington, USA during the summers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
2
18
1
1
Order By: Relevance
“…One approach for assessing river pollution is to use bio-indicators such as benthic diatom and macroinvertebrate communities (Hirst et al 2002;Hering et al 2006;Hughes et al 2012;Namin et al 2013a, b;O'Driscoll et al 2014;Tan et al 2014a). The use of biotic communities for monitoring aquatic environments, especially water quality, has several widely known advantages over physicochemical monitoring (Hering et al 2006;Sharifinia et al 2012a;Findik 2013;Tan et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…One approach for assessing river pollution is to use bio-indicators such as benthic diatom and macroinvertebrate communities (Hirst et al 2002;Hering et al 2006;Hughes et al 2012;Namin et al 2013a, b;O'Driscoll et al 2014;Tan et al 2014a). The use of biotic communities for monitoring aquatic environments, especially water quality, has several widely known advantages over physicochemical monitoring (Hering et al 2006;Sharifinia et al 2012a;Findik 2013;Tan et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Reference species richness was based on detailed surveys and the wide experience of experts, so it represents a level that is not likely to be observed in conventional river health surveys. The importance of sampling effort in large rivers has been investigated and reviewed in many studies (e.g., Bady et al 2005;Flotemersch et al 2006;Hughes et al 2011). Sampling effort is a significant issue, particularly for fish, because practicalities mean that only a small proportion of the total river area is sampled and only a limited time is available for sampling.…”
Section: Considerations For Sampling Methods and Indicator Selectionmentioning
confidence: 99%
“…For each indicator group, the score was weighted by data quality in terms of relative sampling effort (Table 5). Many studies have shown that abundance and diversity continue to increase up to a given sampled area (e.g., Colwell and Coddington 1994;Connor et al 2000;Gotelli and Colwell 2001;van Gemerden et al 2005;Hughes et al 2011). In a comprehensive river health survey, a first step would be to establish the relationship between the value of the chosen index score and the level of sampling effort in order to determine the level of sampling effort at which the index value stabilizes.…”
Section: Computing Weighting and Combining Indicator Scoresmentioning
confidence: 99%
“…Such studies have been conducted for estimating effects on taxa richness (e.g., Cao et al, 2002a;Hughes et al, 2012;Ligeiro et al, 2013) and site and group separation (e.g., Cao et al, 2002a;Ligeiro et al, 2013). In addition, they have been used for evaluating the variability of multimetric indices (MMIs) (e.g., Doberstein et al, 2000;Dolph et al, 2010;Li et al, 2001) and the performance of observed-to-expected (O/E) indices (i.e., RIV-PACS: River Invertebrate Prediction and Classification System) (e.g., Ostermiller and Hawkins, 2004).…”
Section: Introductionmentioning
confidence: 99%